Evolution of agricultural support policies - Zhang, Yumei; Meng, Ting; Lan, Xiangmin; Fan, Shenggen; Chen, Kevin Z.; Si, Wei (2022)
In recent decades, agricultural support policies in many countries have played an active role in promoting food production and reducing hunger and poverty. Remarkable achievements have been made globally in agricultural production, with rapid growth in output of agricultural products outpacing population growth. Populations’ food consumption has increased and the number of undernourished people has decreased significantly. Particularly in China, agricultural reforms that were initiated in the late 1970s have increased farmers’ incomes and improved dietary quality. By 2020, China had achieved a moderately prosperous society in all aspects and had eliminated hunger and poverty. This chapter reviews domestic and international agricultural support policies and their impacts. China's experience of developing agricultural support policies has been summed up in order to, on the one hand, provide a reference for other developing countries. On the other hand, China is now implementing new national development goals of nutrition and health, green and high quality development, common prosperity, and institutional opening. The analysis of the challenges being faced in the course of implementing the corresponding new agricultural support policies can help optimize these policies.